2021
DOI: 10.1007/s42729-021-00498-w
|View full text |Cite|
|
Sign up to set email alerts
|

Changes in Calcareous Soil Activity, Nutrient Availability, and Corn Productivity Due to The Integrated Effect of Straw Mulch and Irrigation Regimes

Abstract: Sustainable agricultural production is mainly attributed to healthy soils. Calcareous soils, especially in arid and semiarid areas, suffer from low organic matter and nutrient availability. Low organic matter could degrade soil with reducing the crop productivity. Thus, the present study aimed to assess the integrated effect of soil mulch and irrigation on soil activity, nutrient availability, and potentiality of corn yield under calcareous soil conditions. In a calcareous soil, two mulching soil treatments (m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 53 publications
(16 citation statements)
references
References 49 publications
0
16
0
Order By: Relevance
“…Unlike, lowering water supply by 40% (ETc60) of normal (ETc100) could negatively influence the properties of the soil. In keeping with this trend, Mubarak et al (2021) have reported that irrigation by 60% of crop evapotranspiration showed reduction in organic matter and carbon and soil activity. Due to the importance of water in promoting soil enzymes produced by microorganisms, water deficiency caused adverse impact on biological activity of soil biota (Hueso et al 2012) and disturbance in the balance of nutrients soil and plant (Kim et al 2008;Saudy and El-Metwally 2019).…”
Section: Discussionmentioning
confidence: 61%
“…Unlike, lowering water supply by 40% (ETc60) of normal (ETc100) could negatively influence the properties of the soil. In keeping with this trend, Mubarak et al (2021) have reported that irrigation by 60% of crop evapotranspiration showed reduction in organic matter and carbon and soil activity. Due to the importance of water in promoting soil enzymes produced by microorganisms, water deficiency caused adverse impact on biological activity of soil biota (Hueso et al 2012) and disturbance in the balance of nutrients soil and plant (Kim et al 2008;Saudy and El-Metwally 2019).…”
Section: Discussionmentioning
confidence: 61%
“…Using plant residues on the soil surface as mulch to provide organic matter, restrain weed growth, suppress erosion and evaporation of water from the soil is the practice of conservation tillage systems. Moreover, conservation tillage using mulch and a good irrigation system will increase plant evapotranspiration, improve soils that contain a lot of lime and promise good productivity results, especially on dry land [23]. Another research stated that the use of organic material rich in essential nutrients will accumulate as a food source in plants which then increases the efficiency of fertilizers entering the soil, better soil absorption and protects the soil from pests and diseases soil fertility status is well maintained [24].…”
Section: Resultsmentioning
confidence: 99%
“…1 Reductions in leaf greenness (SPAD value), spike length (cm), grains weight spike -1 (g) weight of 1000 grains (g), and grain yield (t ha -1 ) of wheat owing to Irr60 and Irr80 compared to full irrigation (Irr100). Irr60, Irr80 and Irr100: irrigation at 60, 80 and 100% of crop evapotranspiration, respectively length, altered stomatal movements, water and mineral nutrition association with decreased plant yield and water use efficiency are the major outcomes of drought (Kumawat and Sharma 2018;Mubarak et al 2021). Photosynthesis activity is decreased primarily by closing of stomata, membrane injury and altered functioning of several enzymes, particularly those which are associated with ATP synthesis (Kumawat and Sharma 2018;Sharma et al 2020a).…”
Section: Discussionmentioning
confidence: 99%